FRI0117 THE COMPARATIVE RISK OF OSTEOPOROTIC FRACTURES AMONG PATIENTS WITH RHEUMATOID ARTHRITIS RECEIVING TNF INHIBITORS VERSUS OTHER BIOLOGICS: A NATION-WIDE COHORT STUDY IN KOREA. (June 2019) - Shin, Anna; Dong, Yaa-Hui; Shin, Seunghwan; Ha, You-Jung; Lee, Yun Jong; Lee, Eun Bong; Song, Yeong Wook; Kang, Eun Ha
Abstract : Background: Rheumatoid arthritis (RA) is associated with an increased risk of osteoporosis and osteoporotic fracture, but little is known about comparative risk of osteoporotic fractures between biologic agents. Objectives: To investigate the comparative risk of osteoporotic fractures among RA patients who initiated TNF inhibitors, abatacept, and tocilizumab. Methods: We identified patients aged ≥ 40 years with at least two ICD-10 diagnosis codes for RA who initiated TNF inhibitor, abatacept, or tocilizumab from the 2005-2015 Korean National Health Insurance Service datasets. The primary outcome was a composite osteoporotic fracture endpoint of spine, hip, forearm or humerus fractures requiring hospitalization. Secondary outcomes were spinal and non-spinal fractures. Follow-up period started from the day after the first dispensing date of the study drug to the earliest date among the following events: discontinuation of the study drugs, outcome occurrence, disenrollment, end of study dataset, or death. Propensity score (PS) matching with a variable ratio of 10:1 was conducted for TNF inhibitor versus abatacept initiators and for TNF inhibitor versus tocilizumab initiators to adjust for baseline confounding. We estimated hazard ratio (HR) and 95% confidence interval (CI) of osteoporotic fracture risks comparing TNF inhibitors to abatacept or tocilizumab by Cox proportional hazard models stratified by a matching ratio. Results: We included 2, 339 TNF inhibitor initiators and 594 abatacept initiators, and 2, 486 TNF inhibitor initiators and 647 tocilizumab initiators in each PS-matched cohort. The incidence rates per 100 person-years for the primary outcome were 1.57 and 1.65 for TNF inhibitor and abatacept initiators, and 1.69 and 2.05 for TNF inhibitor and tocilizumab initiators, respectively. The HR (95% CI) for the primary outcome was 1.10 (1.54-2.23) comparing TNF inhibitors versus abatacept and it was 1.00 (0.53-1.92) comparing TNF inhibitor versus tocilizumab initiators. We also did not find any significant difference for secondary outcomes (Table1 ). Conclusion: We did not find a significant difference in the risk of osteoporotic fractures between TNF inhibitor and abatacept initiators, or between TNF inhibitor and tocilizumab initiators in this Korean population-based cohort study. Disclosure of Interests: None declared